2017
DOI: 10.1111/pbi.12755
|View full text |Cite
|
Sign up to set email alerts
|

High efficient multisites genome editing in allotetraploid cotton (Gossypium hirsutum) using CRISPR/Cas9 system

Abstract: Summary Gossypium hirsutum is an allotetraploid with a complex genome. Most genes have multiple copies that belong to At and Dt subgenomes. Sequence similarity is also very high between gene homologues. To efficiently achieve site/gene‐specific mutation is quite needed. Due to its high efficiency and robustness, the CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 system has exerted broad site‐specific genome editing from prokaryotes to eukaryotes. In this study, we utilized a CRISPR/Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
179
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 233 publications
(188 citation statements)
references
References 64 publications
7
179
0
2
Order By: Relevance
“…Recently, we established the CRISPR/Cas9 ( Streptococcus pyogenes Cas9) system in cotton with high efficiency. Interestingly, no off‐target mutations were detected by targeted deep sequencing in the top 26 potential off‐target sites of four sgRNAs, suggesting that the CRISPR/Cas9 system is an efficient and reliable tool for allotetraploid cotton genome editing (Wang et al ., ). To further investigate the specificity of CRISPR/Cas9 system on the genome‐wide scale in cotton genome editing, three target genes – encoding the AP2/B3‐like transcription factor ( AP2 ), MYB44 transcription factor ( MYB44 ) and nucleotide‐binding (NB)‐ARC domain‐containing disease resistance protein ( ARC ) were edited using CRISPR/Cas9 in this study (Li et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, we established the CRISPR/Cas9 ( Streptococcus pyogenes Cas9) system in cotton with high efficiency. Interestingly, no off‐target mutations were detected by targeted deep sequencing in the top 26 potential off‐target sites of four sgRNAs, suggesting that the CRISPR/Cas9 system is an efficient and reliable tool for allotetraploid cotton genome editing (Wang et al ., ). To further investigate the specificity of CRISPR/Cas9 system on the genome‐wide scale in cotton genome editing, three target genes – encoding the AP2/B3‐like transcription factor ( AP2 ), MYB44 transcription factor ( MYB44 ) and nucleotide‐binding (NB)‐ARC domain‐containing disease resistance protein ( ARC ) were edited using CRISPR/Cas9 in this study (Li et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Multiple types of mutations were detected at the specific on‐target sites (Figure S1a and Table S3). This editing efficiency is comparable to the efficiency (66%–100%) when editing exogenous transgene Discosoma red fluorescent protein ( dsRed2 ) and an endogenous cotton gene GhCLA1 in our recent report (Wang et al ., ). We found no bias on the editing efficiency between At‐ and Dt‐subgenome loci based on WGS data, but different mutation patterns (Figure S1b).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, various genome‐editing methods, particularly methods involving sequence‐specific nucleases (SSNs) for creating targeted double‐strand breaks (DSBs), have emerged as major breakthroughs in site‐specific genome editing (Cong et al ., ; Li et al ., ; Wood et al ., ). In particular, CRISPR/CRISPR‐associated 9 (CRISPR/Cas9) is considered the most simple and effective SSN developed thus far and has been used for genome editing in major crops, including rice (Jiang et al ., ; Miao et al ., ; Shan et al ., ), sorghum (Jiang et al ., ), tobacco (Gao et al ., ), wheat (Shan et al ., ; Wang et al ., ), maize (Liang et al ., ), barley (Lawrenson et al ., ), cotton (Wang et al ., ), tomato (Brooks et al ., ), soya bean (Li et al ., ) and camelina (Jiang et al ., ). To date, few studies have reported successful site‐directed mutagenesis using the Cas9/single‐guide RNA (sgRNA) system in rapeseed (Braatz et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In cotton, the application of CRISPR/Cas9 is still at its infancy. Most recently, multiple sites genome editing through CRISPR/Cas9 system in allotetraploid cotton by targeting arginase ( GhARG ), discosoma red fluorescent protein2 ( DsRed2 ) and chloroplast development ( GhCLA1 ) genes proves that it is highly reliable and effective for cotton genome editing (Wang et al ., ,). It is expected that the potential and applications of CRISPR/Cas9 in cotton genome editing are certain to be further developed over time.…”
Section: Potential Of Crispr/cas9 In Cotton Gene Editingmentioning
confidence: 99%